2010
DOI: 10.1002/jbm.b.31715
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of mesenchymal stem cells behaviors by chitosan/gelatin/pectin network films

Abstract: In this article, the chitosan/gelatin/pectin (CGP) network films were prepared to build appropriate physicochemical and mechanical microenvironment for attachment, proliferation, and differentiation of mesenchymal stem cells (MSCs). Results suggested that the hydrophilicity and mechanical character of CGP composites films could be modulated via adjusting the pectin content in the composites. The investigations of attachment and proliferation behaviors of mesenchymal stem cells (MSCs) on the CGP films were carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…For example, studies by Donzelli et al and George et al showed that collagen scaffolds can induce osteoblast differentiation of MSCs. Similarly, our previous work also found that chitosan/gelatin/pectin composites can improve the osteogenic differentiation capacity of BM‐derived MSCs. Nevertheless, the short degradation time of chitosan/gelatin/pectin composites prevents its applications in bone tissue regeneration.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…For example, studies by Donzelli et al and George et al showed that collagen scaffolds can induce osteoblast differentiation of MSCs. Similarly, our previous work also found that chitosan/gelatin/pectin composites can improve the osteogenic differentiation capacity of BM‐derived MSCs. Nevertheless, the short degradation time of chitosan/gelatin/pectin composites prevents its applications in bone tissue regeneration.…”
Section: Introductionsupporting
confidence: 66%
“…The osteogenic differentiation of MSCs can be also characterized by the calcium deposition level and the expression of type I collagen . Von Kossa and Alizarin Red staining were carried out to evaluate the calcium deposition level after 28 days of cell growth.…”
Section: Resultsmentioning
confidence: 99%
“…Pectin (PEC) is a linear anionic polysaccharide which is incorporated into skeletal structures of plants (e.g., citrus fruit) . PEC and its derivatives have already been studied as biomaterial in membrane, film coatings and scaffolds for skin substitutes to improve cellular interaction and hydrophilicity of structure .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] It is enriched in galacturonic acid and galacturonic acid methyl ester units. 24, 25 Li et al 26 showed that the introduction of pectin could improve the proliferative capacity and osteogenic differentiation of MSCs. 23 Moreover, due to its highly biocompatible and biodegradable nature, pectin serves as a novel biomaterial to modulate cell behaviour; pectin-containing matrices can improve the adhesion and proliferation of osteoblasts.…”
Section: Introductionmentioning
confidence: 99%